HUBUNGAN PENGETAHUAN DAN DUKUNGAN TENAGA KESEHATAN DENGAN KEPATUHAN IBU HAMIL MENGKONSUMSI TABLET ZAT BESI UNTUK MENCEGAH ANEMIA DI PUSKESMAS REJOSO - Nurrochmawati, Ike; Retnoningsih, Tri; Fatimah, Nur Aini (JURNAL SABHANGA, 2023)
Introduction:. Approximately 10% of live births experience complications of postpartum hemorrhage caused by anemia. According to WHO (2O15), globally the prevalence of anemia in pregnant women worldwide is 51.2%. The aim of the study was to determine the relationship between the knowledge and support of health workers and the compliance of pregnant women in consuming iron tablets to prevent anemia at the Rejoso Health Center, Nganjuk Regency, East Java. Method : The research method used is quantitative using a cross sectional approach. The population in the study were all pregnant women in the Rejoso Health Center area, Nganjuk Regency. The sample is 42 respondents. The sampling technique uses simple random sampling technique. Statistical test using the Chi square test